PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, PAJAK DAERAH,DAN BELANJA DAERAH TERHADAP PDRB DI PROVINSI SUMATERA BARAT - Afferina, Delvia; Husein, Ratna; Rahmah, Mutia; Murtala, Murtala (Jurnal Ekonomi Regional Unimal, 2024)
This study aims to examine the effect of general allocation funds, special allocation funds, local taxes, and local expenditures on GRDP. This study uses a combination of cross-sectional data with time series on 19 districts and cities in West Sumatra Province during 2017-2021. The data analysis method used is panel data regression with the help of Eviews 10. The results of this study prove that the General Allocation Fund has a negative and significant effect on GRDP. The Special Allocation Fund, Regional Taxes, and Regional Expenditures have a positive and significant effect on GRDP. The magnitude of the influence of the General Allocation Fund, Special Allocation Fund, Regional Taxes, and Regional Expenditure on GRDP is 99.89%, and the remaining 0.10% is influenced by other variables outside this model. It is recommended to the district and city governments in West Sumatra Province to be able to realize general allocation funds, special allocation funds, local taxes, and regional expenditures properly so that the economy in West Sumatra is stable and the welfare of the community increases.